Experimental investigation on the compressive strength and shrinkage of concrete with pre-wetted lightweight aggregates. (30th November 2017) - Wang, X.F.; Fang, C.; Kuang, W.Q.; Li, D.W.; Han, N.X.; Xing, F.
Highlights: Three types of PLWA with five volume fractions were studied. Internal curing shows great influence in the evolvement of the compressive strength and the shrinkage. PLWA combined with expansive agent is effective in reducing shrinkage. A unified model is presented for the prediction of the compressive strength and shrinkage of concrete with PLWA. Abstract: Experimental studies are presented on the influence of three types of pre-wetted lightweight aggregates (PLWA), through their volume fractions and moisture content, on the compressive strength and shrinkage of concrete and expansive concrete. Via integrated thermal analysis, the hydration degree during 7 d–28 d was found to be increased by the internal curing. The use of PLWA increased the shrinkage at 240 d due to the significant increase in the shrinkage deformation during the age of 28 d–90 d caused by internal curing. The results also suggest that incorporation of 10-Mas. % expansive agent is useful to diminish the shrinkage, especially by its combined use with PLWA. Predictive models for the compressive strength and shrinkage of concrete containing PLWA were discussed and a unified model predicting the compressive strength and shrinkage of concrete containing PLWA was suggested.